Survey on the use of synthetic Food Colors in Food Samples procured from different educational institutes of Karachi city. - Saleem, Nida; Umar, Zahida Nasreen; khan, Seema Ismat (Journal of Tropical Life Science, 2013)
The present study was carried out to find the type of food colors added to various food products especially those vended at or near different educational institutes of Karachi city. Different types of food items were analysed for isolation and identification of the added synthetic food colors. The majority of branded food items contained permitted colors however some foods manufactured locally, contained non-permitted colors. About 11% branded and 44% unbranded food items, respectively, were found with not permitted colors for human consumption. Similarly, 4% branded and 30% unbranded beverages were found unfit due to the presence of prohibited colors. Incidences of the use of non-permitted food colors were higher in case of unorganized food makers. Constant vigilance is needed to ensure that the local manufacturers comply with the regulations of food colors not only in terms of non-permitted food colors but also about the control and limits of permitted food colors. Moreover, consumption of colored food items should also be controlled by making the society aware of the hazardous effects of food colors.